2023
DOI: 10.3390/ph16040553
|View full text |Cite
|
Sign up to set email alerts
|

TEAD Inhibitors Sensitize KRASG12C Inhibitors via Dual Cell Cycle Arrest in KRASG12C-Mutant NSCLC

Abstract: KRASG12C is one of the most common mutations detected in non-small cell lung cancer (NSCLC) patients, and it is a marker of poor prognosis. The first FDA-approved KRASG12C inhibitors, sotorasib and adagrasib, have been an enormous breakthrough for patients with KRASG12C mutant NSCLC; however, resistance to therapy is emerging. The transcriptional coactivators YAP1/TAZ and the family of transcription factors TEAD1-4 are the downstream effectors of the Hippo pathway and regulate essential cellular processes such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Our RNAseq results further reinforced the role of fibroblasts as mediators of resistance to KRAS silencing, detailing the upregulation of cell cycle control, EMT, immune system regulation, and cancer-associated pathways such as KRAS, NOTCH, TGF-β, MYC, and WNT as the main pathways induced by fibroblast-derived factors. Specifically, E2F, MYC, and G2M pathways, frequently found to be downregulated upon KRAS inhibition (Hallin et al, 2020; Tammaccaro et al, 2023) ranked on the top three upregulated biological processes found in KRAS-silenced cells stimulated with fibroblast-conditioned media.…”
Section: Discussionmentioning
confidence: 99%
“…Our RNAseq results further reinforced the role of fibroblasts as mediators of resistance to KRAS silencing, detailing the upregulation of cell cycle control, EMT, immune system regulation, and cancer-associated pathways such as KRAS, NOTCH, TGF-β, MYC, and WNT as the main pathways induced by fibroblast-derived factors. Specifically, E2F, MYC, and G2M pathways, frequently found to be downregulated upon KRAS inhibition (Hallin et al, 2020; Tammaccaro et al, 2023) ranked on the top three upregulated biological processes found in KRAS-silenced cells stimulated with fibroblast-conditioned media.…”
Section: Discussionmentioning
confidence: 99%
“…This very limited clinical benefit has been attributed to intrinsic and acquired resistance mechanisms (31)(32)(33)(34), which has led to increased efforts to explore combination therapies. Besides combinatorial targeting of multiple tumor cell intrinsic pathways (35)(36)(37)(38), early pre-clinical experiments also suggested a potential synergy with immune therapy (6,39).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the upregulation of the YAP/TEAD pathway has been implicated as a mechanism of resistance to KRAS inhibition [125,126]. Combination therapies with TEAD inhibitors synergize with KRAS inhibitors by blocking the cell cycle [127]. Combining the mTOR inhibitor vistusertib with MRTX849 treatment showed strong synergy against a panel of sensitive cell lines and xenograft models [50].…”
Section: Reactivation Of the Ras Pathway Or Alternative Signalingmentioning
confidence: 99%
“…SHP2 inhibitors synergize with KRAS G12C inhibitors against sensitive mouse tumors, possibly because they prevent feedback reactivation driven by the loss of ERK-mediated EGFR repression when KRAS activity is abrogated and/or because SHP2 inhibitors drive KRAS to be in the G12C inhibitor-sensitive GDP-bound state of KRAS [50,133]. An alternative preclinical strategy being tested is combining inhibitors of TEAD proteins with KRASi, preventing feedback reactivation [125,127].…”
Section: Combination Therapiesmentioning
confidence: 99%